Clinical Research on the Combination of Unaccompanied and Family-Based Care Models for Premature Infants - Diaoyan, Gao; Taotao, Fan; Chunmei, Yan; Yuanyuan, Tian; Xiaoyan, Liu; Li, Zhang (British Journal of Healthcare and Medical Research, 2026)
Objective: To explore the application effect of the combination of unaccompanied care and family-based care in preterm infants and to provide clinical evidence for optimizing the care program for preterm infants. Methods: A total of 120 preterm infants admitted to the neonatal Intensive Care Unit (NICU) of our hospital from January 2021 to January 2024 were selected as the research subjects and randomly divided into the observation group and the control group, with 60 cases in each group using the random number table method. The observation group adopted a combined model of "unaccompanied basic care + staged family participation". The control group adopted the traditional simple unaccompanied care model. The length of hospital stay, rate of weight gain, incidence of complications (necrotizing enterocolitis, bronchopulmonary dysplasia, etc.), success rate of breastfeeding, score of parental care ability and score of parent-child attachment relationship of the two groups of children were retrospectively analyzed and compared, and growth and development after discharge were evaluated in combination with 3-year follow-up data. Statistical analysis was performed using SPSS 22.0 software, and measurement data were expressed as (x youdaoplaceholder3 ±s) for t-test; Count data were expressed as [n (%)] and analyzed by x-test2. A P value <0.05 was considered statistically significant. Results: The average length of hospital stay in the observation group was (29.8±5.6) days, significantly shorter than that in the control group [(36.5±6.2) days] (t=6.324, P<0.001); The rate of weekly weight gain in the observation group was (19.5±3.1) g/d, significantly higher than that in the control group, which was (14.2±2.8) g/d (t=9.751, P<0.001). The total complication rate in the observation group was 11.6% (7/60), significantly lower than 28.3% (17/60) in the control group (X2=5.792, P=0.016); The success rate of breastfeeding in the observation group was 81.6% (49/60), significantly higher than 56.7% (34/60) in the control group (X2=9.072, P=0.003). The scores of parental care ability (85.6±6.3) and parent-child attachment relationship (88.4±5.7) in the observation group were significantly higher than those in the control group (62.3±7.5) and (65.2±6.8) (t values were 18.963 and 20.154, respectively; P <0.001). The 3-year follow-up showed that 91.6% (55/60) of preterm infants in the observation group had growth and development indicators within the normal range of children of the same age, significantly higher than 73.3% (44/60) in the control group (X2=7.023, P=0.008). Conclusion: The combination of unaccompanied and family-based care model can not only ensure the safety of acute phase treatment for preterm infants, but also promote their growth and development and the improvement of family care ability through family participation, and at the same time strengthen the emotional bond between parents and children, and is suitable for the whole-course care of preterm infants.